1997
DOI: 10.1159/000171623
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback Therapy for Defecation Disorders

Abstract: Biofeedback therapy is a useful adjunct to conventional treatment for many patients with refractory defecation disorders. This article provides an overview regarding the historical evolution of this treatment together with current perspectives regarding the principles and techniques of performing biofeedback therapy and an assessment of its outcome in adults and pediatric patients with defecation disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 38 publications
0
53
0
1
Order By: Relevance
“…For example, Hay-Smith suggested that the regimen should consist on 3 sets of 8 to 12 tonic contractions sustained for 8 to 10 seconds each, and performed 3 times a day; these must be continued for 15 to 20 weeks (20). Munoz -Bono reported that the treatment protocol for faecal incontinence might vary from 1 to 15 sessions, which is due to the difference in learning and comprehension between patients, as stated by Rao (21,22). Gilliland goes even further and states that BFB effectiveness seems to be related to the number of sessions (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hay-Smith suggested that the regimen should consist on 3 sets of 8 to 12 tonic contractions sustained for 8 to 10 seconds each, and performed 3 times a day; these must be continued for 15 to 20 weeks (20). Munoz -Bono reported that the treatment protocol for faecal incontinence might vary from 1 to 15 sessions, which is due to the difference in learning and comprehension between patients, as stated by Rao (21,22). Gilliland goes even further and states that BFB effectiveness seems to be related to the number of sessions (23).…”
Section: Discussionmentioning
confidence: 99%
“…The partnership between patient-physiotherapist: a) increases patient satisfaction and improves compliance and adherence to treatment, b) lets a rapid recognition of pelvic floor muscle exercises (13), and c) enhances learning and comprehension of exercises, since the number of sessions are dependent on patients motivation and cognitive level (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Children with severe constipation were treated with rectal stimulant laxatives or enemas. Before and after each biofeedback training session, parents and the children received psychosocial intervention, including: (1) daily registration; (2) toilet training and anal sphincter exercises (squeeze and push to increase rectal sensitivity, and squeeze in endurance to improve muscle strength); (3) behavioral modification techniques; (4) positive approach; (5) demystification (explanation of relationship between constipation, fecal incontinence, and child behavior); (6) individual psychosocial analysis (using DSM classifications to characterize the child) [19]; (7) biofeedback training (biofeedback training is based on operant conditioning [9,15] and is described in detail elsewhere [2,9,14,19,20]). The number of training sessions varies from 3 to 9 consecutive weeks (average number of six sessions).…”
Section: Methodsmentioning
confidence: 99%
“…Biofeedback has been used in the treatment of FI with variable results [17][18][19][20]. Electric stimulation or neuromodulation of the pelvic floor has also been used in the treatment of idiopathic FI.…”
Section: Introductionmentioning
confidence: 99%